Cost-effectiveness of rotavirus vaccination in Mozambique - Lourenço Guimarães, Esperança (2022)
Funding Information: The authors received funding from Bill and Melinda Gates Foundation (OPP1147721), through PATH subaward number: GAT.2111-01707508-SUB. Funding Information: We thank the EPI and the NITAG, from Mozambique for their support and commitment to the present analysis. We also thank PATH team for the technical support and Laura Kallen (from PATH) for linguistic revision of the manuscript. The authors received funding from Bill and Melinda Gates Foundation (OPP1147721), through PATH subaward number: GAT.2111-01707508-SUB. Publisher Copyright: © 2022 The Authors